Socioeconomic Impact of Small Hydropower on Rural Livelihoods in Sarawak : Insights From Japan’s Experience - Then, Yi Lung; Henry Ho, Law Yih; Abadi, Chanik (2025)
The study investigates the socioeconomic impacts of the Small Hydropower Project (SHP) on Kampung Assum and Kampung Parang villages, focusing on changes in income levels, occupational patterns, and the adoption of lighting and electrical appliances. Specifically, it examines shifts in income distribution, job structures, and access to information and communication technology before and after SHP installation. By evaluating these factors, the study aims to understand how electrification has influenced rural development and living standards in both areas. According to our findings, Kampung Assum achieved a quality of life index of 1.1, slightly higher than Kampung Parang’s index of 1.05. This index is based on the Ohito community in Japan, designed for populations under 500 people (similar to the two local communities).